2018
DOI: 10.1016/j.pscychresns.2018.10.001
|View full text |Cite
|
Sign up to set email alerts
|

Association between olanzapine treatment and brain cortical thickness and gray/white matter contrast is moderated by cholesterol in psychotic disorders

Abstract: I would like to first and foremost acknowledge the contribution from all study participants for contributing with their time and providing valuable data for our research. I am very grateful to Professor Vidar M. Steen, my main supervisor, for including me in his research group, for allowing me the chance to take my PhD and the time to mature. I am also grateful to Professor Ingrid Melle, my co-supervisor, for her extensive knowledge of clinical areas and statistics. She has, without doubt, challenged me the mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 272 publications
1
8
0
Order By: Relevance
“…In this study, cortical thinning in medicated patients relative to unmedicated patients provided preliminary evidence indicating negative effects of mid-to long-term atypical antipsychotic treatment on cortical thickness. Our results were consistent with studies showing the contribution of atypical antipsychotics to cortical thinning in the frontal, temporal, and parietal lobes, which has been repeatedly reported (Lesh et al, 2015;Zhang et al, 2018;Guo et al, 2019;Liu et al, 2020), and in the lateral orbitofrontal cortex (Gjerde et al, 2018;Akudjedu et al, 2020). Mid-to long-term treatment effects may be negative as a result of cumulative pharmacologic effects (Xiao et al, 2018).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In this study, cortical thinning in medicated patients relative to unmedicated patients provided preliminary evidence indicating negative effects of mid-to long-term atypical antipsychotic treatment on cortical thickness. Our results were consistent with studies showing the contribution of atypical antipsychotics to cortical thinning in the frontal, temporal, and parietal lobes, which has been repeatedly reported (Lesh et al, 2015;Zhang et al, 2018;Guo et al, 2019;Liu et al, 2020), and in the lateral orbitofrontal cortex (Gjerde et al, 2018;Akudjedu et al, 2020). Mid-to long-term treatment effects may be negative as a result of cumulative pharmacologic effects (Xiao et al, 2018).…”
Section: Discussionsupporting
confidence: 92%
“…Due to the challenges of conducting clinical trials to study atypical antipsychotic effects for more than 1 year, observations mostly come from cross-sectional studies and longitudinal studies with naturalistic designs. For example, crosssectional studies of SZ patients undergoing current or chronic (over 5 years) treatment suggest cortical loss (Haijma et al, 2013;Lesh et al, 2015;Gjerde et al, 2018;van Erp et al, 2018;Di Sero et al, 2019;Liu et al, 2020). Similar results were observed in BD patients (Gildengers et al, 2014;Birner et al, 2020), although other studies failed to replicate the finding, possibly due to differences in the duration (short, medium and long-term) of atypical antipsychotic treatment and variability in methodology and sample size (Hallahan et al, 2011;Hafeman et al, 2012;Hibar et al, 2018).…”
Section: Introductionmentioning
confidence: 80%
“…In addition, both subgroups of FEPs had lower HDL levels than the HCs. Suboptimal levels of HDL, apart from increasing the risk of CVD complications [ 37 ], have been considered to play a role on brain myelination, with an increase of negative symptoms [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Impairments in myelination and synaptic communication have likewise been established in the pathophysiology of schizophrenia and related psychosis (71)(72)(73), and studies have further demonstrated sex difference in white matter abnormalities and its association with symptoms in schizophrenia (74). Given that antipsychotic drugs stimulate lipid biosynthesis with possible effects on myelin-related structures (24,26,75,76) and that estrogen regulates the synthesis of structural proteins essential for cholesterol formation (77), it is plausible that these two pathways interact to improve symptoms of psychosis. Supporting such an interpretation is that impairments in estrogen-and lipid metabolism have been implicated in the development of and in predicting the severity of schizophrenia (3,11,(78)(79)(80)(81)(82)(83).…”
Section: Discussionmentioning
confidence: 99%